Selection of Guiding Plate Combined With Surgical Navigation for Microsurgical Mandibular Reconstruction. Issue 4 (June 2020) - Yu, Yao; Zhang, Wen-Bo; Liu, Xiao-Jing; Guo, Chuan-Bin; Yu, Guang-Yan; Peng, Xin
Abstract : Purpose: The present study summarized selection of guiding plate combined with surgical navigation for microsurgical mandibular reconstruction. Methods: Data from preoperative maxillofacial enhanced computed tomography (CT) scans were imported to ProPlan CMF. The authors performed virtual mandibulectomy and superimposed 3-dimensional (3D) iliac images on mandibular defects. Guiding plates including mandibular fixation device, reconstruction plate, guiding model, and occlusal splint for various mandibular hemimandibular central lateral (HCL) defects were fabricated to fix bilateral residual mandible. The model was scanned, and data were imported into ProPlan CMF and the intraoperative navigation system. Through landmark points upon the guiding plate, position of the residual mandible was determined during surgical navigation. Intraoperative navigation was used to implement the virtual plan. Sagittal, coronal, axial, and 3D reconstruction images displayed by the navigation system were used to accurately determine osteotomy sites and osteotomy trajectory during surgery. Surgical probe guidance was used to mark the osteotomy line and transfer the virtual procedure to real-time surgery. Accuracy was evaluated using chromatographic analysis. Results: Different guiding plates combined with surgical navigation could be used for various mandibular defects, including mandibular fixation devices for LCL defects, reconstruction plates for LC/L/C defects, and guiding models and occlusal splints for H/L/LC defects (including mandibular ramus). In our study, average and largest shift of the mandible and osteotomy site was <5 mm. Conclusion: The authors summarized different ways of combining guiding plates with surgical navigation for reconstruction of various mandibular defects, which could improve clinical outcomes of this procedure with high accuracy. Abstract : Supplemental Digital Content is available in the text